2023
DOI: 10.1002/adfm.202302483
|View full text |Cite
|
Sign up to set email alerts
|

Dendri‐LEC Family: Establishing the Bright Future for Dendrimer Emitters in Traditional and Graphene‐Based Light‐Emitting Electrochemical Cells

Luca M. Cavinato,
Keiko Yamaoka,
Sophia Lipinski
et al.

Abstract: A rational implementation and optimization of thermally activated delayed fluorescent (TADF) dendrimer emitters in light‐emitting electrochemical cells (LECs) sets in the Dendri‐LEC family. They feature outstanding stabilities (90/1050 h for green/yellow devices) that are comparable to the best green/yellow Ir(III)‐complexes (450/500 h) and conjugated polymers (33/5500 h), while offering benefits of low‐cost synthesis and easy upscaling. In particular, a fundamental molecular design that capitalizes on exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…1,12–27 Their basic photophysical properties have been well documented in many excellent reviews and previous studies. 28–38 The first generation OLEDs were based on fluorescent emitters (emission comes only from the S 1 state after excitation), which harvest only 25% of singlet excitons and therefore the maximum internal quantum efficiency (IQE) was only 25%, since 75% of triplet excitons are in the dark. The external quantum efficiency (EQE) of an OLED device depends on the IQE and is related to each other as follows: 9 η EQE = η IQE × η out = ( γ × η γ × Φ PL ) × η out where η IQE and η out denote the internal quantum efficiency and the light-out-coupling efficiency, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1,12–27 Their basic photophysical properties have been well documented in many excellent reviews and previous studies. 28–38 The first generation OLEDs were based on fluorescent emitters (emission comes only from the S 1 state after excitation), which harvest only 25% of singlet excitons and therefore the maximum internal quantum efficiency (IQE) was only 25%, since 75% of triplet excitons are in the dark. The external quantum efficiency (EQE) of an OLED device depends on the IQE and is related to each other as follows: 9 η EQE = η IQE × η out = ( γ × η γ × Φ PL ) × η out where η IQE and η out denote the internal quantum efficiency and the light-out-coupling efficiency, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[13] A number of reports on the employment of TADF emitters in LEC devices can be found in the scientific literature, and although these devices, in some cases, deliver promising emission efficiency, they also invariably feature broad emission spectra. [14] Karaman et al recently reported on the synthesis of two cationic MR-TADF compounds, which comprised a DiKTa [15] core endowed with a chemically grafted imidazolium cation that is charge-compensated by a mobile PF 6 − anion. [16] They introduced a neat thin film of one, or a blend, of these two ionic compounds as the active material in an LEC device, which produced electroluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such success is accompanied by the inferior host–guest energy transfer, low charge transport, serious phase segregation, and many others. Recently, aiming to suppress fluorescence quenching, a steric-inhibition method has been proposed for TADF emitters. Although some TADF molecules with dendritic structures have been designed with multiple generations of donors or acceptors, such a method usually demands complicated synthetic routes. …”
mentioning
confidence: 99%